Classification of Fixed Point Network Dynamics from Multiple Node Timeseries Data - Blaszka, David; Sanders, Elischa; Riffell, Jeffrey A.; Shlizerman, Eli (Frontiers in Neuroinformatics, 2017)
Fixed point networks are dynamic networks encoding stimuli via distinct output patterns. Although such networks are common in neural systems, their structures are typically unknown or poorly characterized. It is thereby valuable to use a supervised approach for resolving how a network encodes inputs of interest and the superposition of those inputs from sampled multiple node time series. In this paper, we show that accomplishing such a task involves finding a low-dimensional state space from supervised noisy recordings. We demonstrate that while standard methods for dimension reduction are unable to provide optimal separation of fixed points and transient trajectories approaching them, the combination of dimension reduction with selection (clustering) and optimization can successfully provide such functionality. Specifically, we propose two methods: Exclusive Threshold Reduction (ETR) and Optimal Exclusive Threshold Reduction (OETR) for finding a basis for the classification state space. We show that the classification space -- constructed through the combination of dimension reduction and optimal separation -- can directly facilitate recognition of stimuli, and classify complex inputs (mixtures) into similarity classes. We test our methodology on a benchmark data-set recorded from the olfactory system. We also use the benchmark to compare our results with the state-of-the-art. The comparison shows that our methods are capable to construct classification spaces and perform recognition at a significantly better rate than previously proposed approaches.